Profile Comparison of Patients with Staphylococcus aureus and Staphylococcus haemolyticus on Pus Specimen at Dr. Moewardi Hospital - MAHARANI, AMANDA DIAH; ., Marwoto; Nefihancoro, Udi Heru (Nexus Kedokteran Klinik, 2016)
Introduction: Staphylococcus aureus and Staphylococcus haemolyticus were some of bacteria that often found in pus specimen. Unlike S. aureus, which is true pathogen, S. haemolyticus which is known by opportunistic bacteria were not considered as caused of infection. Therefore, the need of comparative data that can determine whether S. haemolyticus were cause of infection or just colonization was necessary. The purpose of this research is to compare clinical profile of patientsâ with S. aureus and S. haemolyticus found in pus specimen. Methods: This study was a descriptive research using cross-sectional approach. The object of the research were patientsâ medical records which have been identified by pus culture with positive result of Staphylococcus aureus and Staphylococcus haemolyticus on 2013-2014. Sampling was held during November and December 2015 at Dr. Moewardi Hospital, Surakarta with inclusion and exclusion criterias. Sampling was done and 69 people taken from the population. The data was statically analyzed by frequency distributive technique. Result: In 2 years, it is found that patients with Staphylococcus aureus and Staphylococcus haemolyticus are dominantly by men. Most of patients are adult (19-65 years old). Body temperature of patients with Staphylococcus aureus risk 2,04 times of increasing than patients with Staphylococcus haemolyticus. Conclusions: There are differences in clinical profile of patient with Staphylococcus aureus and Staphylococcus haemolyticus on pus specimen at Dr. Moewardi Hospital. Keywords: Pus Specimen, Pus Culture, Staphylococcus aureus, Â Staphylococcus haemolyticus